Pengaturan Perubahan Kesalahan Kata Pada Penulisan Komparisi Akta Notaris - Putu Indira Yustika Kusuma Dewi; I Wayan Novy Purwanto (Jurnal Interpretasi Hukum, 2025)
Correction of errors in writing the "komparisi" must follow the procedures stipulated in the applicable laws and regulations, as essentially what is contained in an authentic deed must be accurate to maintain the power of the authentic deed as evidence. This is the duty of the Notary because the Notary must ensure that the documents of the appearing parties, such as identities and supporting evidence, are correct. The purpose of this writing is to understand the regulatory provisions for changing errors in the writing of the "komparisi" in deeds and the legal impacts on Notaries and the parties involved if errors in the "komparisi" writing are not promptly corrected. This journal uses a normative legal research method, including legislative, conceptual, and analytical approaches, due to ambiguities in the norms. The result of this research is that if there are typographical errors in the "komparisi," the Notary corrects them through the renvooi mechanism before the deed is signed or by a correction (ralat) after signing, following the UUJN procedures with the consent of the parties, even though the change of errors in the "komparisi" is not explicitly regulated. The legal impact on the parties for such errors, if not immediately corrected, is that the deed will be degraded to a private deed, and the responsible Notary may be subject to civil, administrative, and criminal sanctions.